2022
DOI: 10.1186/s12877-022-03167-4
|View full text |Cite
|
Sign up to set email alerts
|

Carers using assistive technology in dementia care at home: a mixed methods study

Abstract: Introduction Informal carers support persons with dementia to live at home, even with deteriorating physical, social and cognitive issues. This study aims to examine the experiences and impact of Assistive Technology (AT) on carers, providing care for a person with dementia. Methods This is an explanatory sequential mixed methods study. The quantitative phase was an online and postal survey using the Carers Assistive Technology Experience Questionn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…In the context of dementia care, assistive technology has demonstrated potential to address some of the long-term care needs of PLWD and their carers [ 3 ] and can engage with a consumer-driven model that promotes ‘active ageing’ and/or improvements to participation and quality of life for PLWD [ 5 ]. For carers, benefits of assistive technology can include a reduction in the demands of caring, more opportunities for enjoyment and meaningful activities, and reduced stress [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the context of dementia care, assistive technology has demonstrated potential to address some of the long-term care needs of PLWD and their carers [ 3 ] and can engage with a consumer-driven model that promotes ‘active ageing’ and/or improvements to participation and quality of life for PLWD [ 5 ]. For carers, benefits of assistive technology can include a reduction in the demands of caring, more opportunities for enjoyment and meaningful activities, and reduced stress [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, there has been a growth in research examining the role that digital technologies can play as a tool to support carers by compensating for the functional cognitive and physical decline on the PLWD’s capacities to engage in everyday life [ 6 – 8 ]. Emerging technology may also play a key role in addressing broader social issues arising from population ageing, including a shortage of care staff and high care costs associated with older adults living within formal residential care settings [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach allows researchers to gain a more comprehensive and nuanced understanding of a research problem. Previous mixed-method studies that reported the usefulness of DAT mainly focused on well-being [ 24 ], counselling [ 25 ], social participation [ 26 ], and activity monitoring [ 27 ]. However, there is a lack of mixed-method studies focusing on time management.…”
Section: Introductionmentioning
confidence: 99%